Perceived Threat among University Students of Ethnic Diversity - Mahdi, Ali Maleh; Soleimani, Esmaiel (Journal of Cultural Analysis and Social Change, 2026)
This research aims to determine the extent of the impact of perceived threat, both symbolic and realistic, on the students of the University of Kirkuk. The study sought to clarify the feelings of threat or lack of security among the students of the University of Kirkuk and its effect on their social, cultural, and physical life paths, and whether these factors could directly or indirectly influence the student’s psychological state. The importance of this study stems from the reality of the ethnic diversity that characterizes Kirkuk Governorate, where differences in the levels of perceived threat among the ethnic groups are observed. This necessitates studying the psychological and social factors underlying this variation. The current study aims to: 1. Identify the level of perceived threat among university students. 2. Identify the differences in the degree of perceived threat (both symbolic and realistic) according to the variable of ethnicity (Arab, Turkmen, Kurdish). To achieve this goal, the researcher divided it into two branches: a. Identify the differences in the degree of perceived symbolic threat according to the variable of ethnicity (Arab, Kurdish, Turkmen). b. Identify the differences in the degree of perceived realistic threat according to the variable of ethnicity (Arab, Kurdish, Turkmen). The study relied on the descriptive method, with data analyzed using appropriate statistical techniques. As for the measurement tool, the researcher developed a Perceived Threat Scale based on the Integrated Threat Theory, which was adopted for both construction and interpretation. The research findings revealed the following: 1. University students experience both symbolic and realistic perceived threats, and the value of the symbolic threat was higher than that of the realistic threat. 2. Regarding differences among ethnic groups, the results of the study showed that: a. There are statistically significant differences among the ethnic groups (Arab, Kurdish, Turkmen) in symbolic perceived threat, in favor of the Arab group. b. There are no statistically significant differences among the ethnic groups (Arab, Kurdish, Turkmen) in the level of realistic perceived threat.